Pedagogical innovation in higher education and active learning methodologies – a case study. Issue 2 (27th November 2020) - Carvalho, Andreia; Teixeira, Sergio Jesus; Olim, Leonilde; Campanella, Sancha de; Costa, Teresa
Abstract : Purpose: The aim of this study is to obtain a broader knowledge of innovative pedagogical practices in higher education, by analysing the particular case of the Higher Institute of Administration and Languages (ISAL). The literature review reveals a gap in this scientific field, and filling this gap is as imperative as the need to articulate higher education with the Students' Profile by the End of Compulsory Schooling. Design/methodology/approach: This research adopts a qualitative methodological approach, in order to analyse the students and teachers' perceptions of the active learning methodologies implemented at ISAL. Data were collected from a closed-ended questionnaire, aimed at a population composed of students and teachers. Findings: The literature review reveals a gap in this scientific field, particularly in Portugal. Filling this gap is as imperative as the need to articulate higher education with the Students' Profile by the End of Compulsory Schooling. Practical implications: With the adoption of this methodological approach, this research intends to verify not only whether the innovative pedagogical practices addressed in the literature review are implemented in this institution, but also to identify obstacles to their implementation. With regard to the results, several pedagogical innovation practices are already implemented, even though some limitations to their implementation are identified. Originality/value: This research allows identifying indicators that are essential to outline an intervention plan in the pedagogical practices implemented at ISAL or other higher education institutions and contributes to assessing the current state of pedagogical practices in higher education.